Myrtus Communis Ameliorates Ionizing Radiation-Induced Cardiopulmonary Injury in Rats: Trod-Grog Study - Aytekin, Aynur; Isci, Oguzhan; Ozyilmaz, Nagehan; Karaoglu, Sumeyye Yilmaz; Ertas, Busra; Sen, Ali; Atasoy, Beste Melek; Yılmaz Karaoğlu, Sümeyye (Keai Publishing Ltd, 2026)
Objectives: Ionizing radiation (IR), widely used in diagnostic and therapeutic procedures, can damage vital organs such as the heart and lungs through oxidative stress. This study aims to assess the potential radioprotective effect of Myrtus communis (MC) against cardiopulmonary injury. Methods: Thirty female rats were divided into four groups. Control (C) and IR (R) groups received oral saline. The treatment (R+MC) and pretreatment (R+preMC) groups received MC (100 mg/kg) for 4 days (starting on the day of IR) and 8 days (starting 4 days before IR), respectively. All IR-exposed groups (R, R+MC, R+preMC) received a single 10 Gy whole-body irradiation. Histopathological changes were assessed by hematoxylin-eosin staining, while oxidative stress was evaluated by measuring malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO), nitric oxide (NO), superoxide dismutase (SOD), glutathione S-transferase (GST), and tissue factor activity (TFa) levels. Protein profiles in tissues were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Results: Histopathologically, MC reduced alveolar and cardiomyocyte damage in both R+MC and R+preMC groups. IR increased all oxidative stress markers and decreased antioxidant parameters in heart and lung tissues (p < 0.05-0.001). Both MC treatment and pretreatment reversed these effects, significantly reducing oxidative/inflammatory markers and restoring antioxidant enzyme activities (p < 0.05-0.001). The R+preMC group demonstrated a stronger protective effect than the R+MC group. Conclusion: Our study shows that MC has a radioprotective effect on the cardiopulmonary system by decreasing oxidative damage. MC appears to be a promising natural compound for advanced radioprotection research, and further molecular and clinical studies could clarify its mechanisms and potential applications.
Keywords: Heart; Ionizing Radiation; Lung; Myrtus Communis; Oxidative Stress; Radioprotection; Rats